A poética de Aristóteles: conceito e racionalidade - Penna, Tiago (2017)
In Aristotle, art (tekhné) refers first to the (i) disposition or "power" (dýnamis) of the soul (psyché) related to production (poiésis), and therefore can be understood as rational, that is, a kind of skill or acquired habit (héxis), related to poetic making (poiésis), which establishes itself in the poet as a kind of productive habit (héxis poietikê) with-by poems, the art (techné) that resides on the artist. On the other hand, from the epistemological point of view, the Poetics - specifically - constitutes (ii) a particular science (epistême), inserted in the genre of the poietic or "productive" sciences (epistême poietikê), whose own method distinctive is capable of analyzing tragic poetry, from the formal point of view, and therefore of its constituent elements. Thus, when conceived as a science (epistème), its methodological approach must adapt, and therefore, admit some margin of "fluctuation" consistent with the degree of "variation" of its object. Therefore, for us, poetic art can also be conceived as an authentic genre of rationality, having in view its singularities and peculiarities as a specific genus of discursiveness (lógos), capable of science (epistême), even if structured in order to account from the singularity of his object of study, poetry, or poetic lógos, rationally re-known through formal analysis of the constituent elements of the singular poems. For this, Aristotle studies methodological considerations in the course of his corpus, which allow us to consider - by analogy - that: Poetics consists of a kind of authentic rationality inherent in poetry, and therefore should be considered as a specific genus of discursiveness (lógos), alongside analytical, dialectic, and rhetoric. And yet, that Poetics as science is also supported ontogenetically and epistemically - by hypothesis - by the genre of poietic or productive rationality (dianóia poietikê).